1988
DOI: 10.1266/jjg.63.523
|View full text |Cite
|
Sign up to set email alerts
|

Restriction endonuclease analysis of chloroplast DNA from A-genome diploid species of rice.

Abstract: Relationships between chloroplast genomes (=ctDNAs) from diploid, Agenome species of rice ( Oryza spp.) were established using length differences in restriction fragments of ctDNAs.Five out of 11 endonucleases used revealed differences in ctDNA fragment lengths among 19 accessions of the cultivated species, 0. sativa and 0. glaberrima.A larger sample of ctDNAs from 66 accessions of both wild and cultivated species were analyzed with three of those five endonucleases, resulting in the identification of nine typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The other is that the changes in the chromosomal structure during differentiation in indica proceeded much faster than in japonica. These cytological studies indicate the presence of independent diphyletic or polyphyletic domestication of O. sativa, that had been previously suggested based on isozyme and molecular studies (e.g., Ishii et al 1988, Cheng et al 2003. Application of these FISH studies to ancestral wild relatives of O. sativa and other species in the AA genome of the genus Oryza may contribute to further elucidating the history of rice domestication and that of speciation in the genus Oryza.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The other is that the changes in the chromosomal structure during differentiation in indica proceeded much faster than in japonica. These cytological studies indicate the presence of independent diphyletic or polyphyletic domestication of O. sativa, that had been previously suggested based on isozyme and molecular studies (e.g., Ishii et al 1988, Cheng et al 2003. Application of these FISH studies to ancestral wild relatives of O. sativa and other species in the AA genome of the genus Oryza may contribute to further elucidating the history of rice domestication and that of speciation in the genus Oryza.…”
Section: Discussionsupporting
confidence: 61%
“…O. sativa is classified into two subspecies, japonica and indica, with a third group javanica classified as a tropical component of the subspecies japonica (Oka 1958). The genetic diversity of japonica and indica has been investigated based on morpho-physiological traits (Oka 1958), isozymes (Second 1982, 1985, Glaszmann 1987, and nucleic and cytoplasmic molecular markers (e.g., Ishii et al 1988, Wang and Tanksley 1989, Zhang et al 1992, Suh et al 1997, Bautista et al 2001, Sun et al 2001, Cheng et al 2003, and in these studies it was reported that genetic diversity was higher in indica than in japonica.…”
Section: Introductionmentioning
confidence: 99%
“…3). This result is compatible with the hypothesis that O. sativa is originated from O. rufipogon (Oka and Chang, 1959 (Second, 1982;Ishii et al, 1988;Cheng et al, 2003). This article is contribution number 598 from the Laboratory of Plant Genetics, Graduate School of Agriculture, Kyoto University.…”
Section: Discussionsupporting
confidence: 88%
“…The domestication process of O. sativa has been proposed to be either monophyletic (Oka and Chang, 1962) or diphyletic (Second, 1982). The endonuclease analysis of chloroplast DNA by Ishii et al (1988) strongly suggested diphyletic domestication since the two major chloroplast genome types found in O. sativa are likely to have originated independently from the corresponding types in O. rufipogon. Wang et al (1992) investigated the phylogenetic relationships based on RFLP analysis of nuclear DNA.…”
Section: Introductionmentioning
confidence: 99%